GAYA KEPEMIMPINAN TERPADU KEPALA SEKOLAH DALAM MENGELOLA LEMBAGA PENDIDIKAN ISLAM - Rastina; Muchammad Eka Mahmud; Akhmad Muaddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the integrated leadership model practiced by school principals in managing Islamic educational institutions, particularly in addressing leadership challenges that remain evident across various educational settings. The main issue that underpins this research is the limited effectiveness of leadership, which contributes to suboptimal organizational performance and weak decision making processes. The purpose of this study is to provide a comprehensive understanding of leadership models that are relevant for school principals, as well as to explain how an integrated leadership approach can support the improvement of Islamic educational institutions. This research employs a qualitative method using library research, while data analysis is carried out through content analysis of selected literature published between 2021 and 2026. The findings show that integrated leadership combining transformational, transactional, situational, participatory, and prophetic models offers a positive influence on work culture, teacher motivation, and overall institutional effectiveness. Each leadership model contributes distinct strengths, ranging from vision reinforcement and performance monitoring to managerial flexibility, collaborative decision making, and the promotion of moral and spiritual values. Overall, the study concludes that integrated leadership is a relevant, adaptive, and holistic approach for responding to the dynamic challenges faced by Islamic educational institutions, while simultaneously supporting sustainable quality improvement.